(untitled) (International journal of artificial intelligence, 2026)
Leukodystrophies are a heterogeneous group of rare, inherited neurological disorders characterized by progressive degeneration of the cerebral white matter due to abnormal myelin formation or maintenance. These disorders predominantly affect children and lead to severe motor, cognitive, and behavioral impairments. This article provides an overview of the clinical manifestations, genetic background, and neuroimaging features of leukodystrophies, with particular emphasis on their impact on neurodevelopmental outcomes. Advances in molecular genetics and magnetic resonance imaging have significantly improved diagnostic accuracy, allowing earlier identification and better prognostic evaluation. Understanding the complex pathophysiology of leukodystrophies is essential for timely diagnosis, appropriate management, and genetic counseling.